Two new polyoxometalate-based transition metal complexes inhibit bladder cancer cell growth via mitochondrial apoptotic pathway. Issue 10 (19th May 2019) - Xiao, Huiyuan; Wu, Baojun; Xue, Chunxiao; Wang, Fan
Abstract: Two new polyoxometalate (POM)-based transition metal complexes, [Ag2 (p-H2 pyttz)2 ][H2 SiMo12 O40 ]·6H2 O (1, H2 itpy = 4-(5-(1H-imidazol-2-yl)-1H-1, 2, 4-triazol3-yl)pyridine) and [Cu5 (m-pyttz)2 (H2 O)2 ][H3 SiMo12 O40 ] (2, H2 pyttz = 3-(pyrid-3/4-yl)-5(1H-1, 2, 4triazol-3-yl)-1, 2, 4-triazolyl), have been hydrothermally synthesized by using Keggin-type POM anion [SiMo12 O40 ] 4– and different N-donor organic compounds as building blocks. The in vitro antitumor activities of1 and2 were screened on cancer cell lines (MDA-MB-231, CHO, MIA-PaCa-2, J82, HCT-8 and HeLa) and normal cell line (HEK-293). Both compounds exhibited significant antitumor activities, especially against J82 bladder cancer cells. Annexin V/PI was used to detect the apoptosis levels in J82 cell lines. The western blot, ROS (Reactive oxygen species) analysis and mitochondrial membrane potential (ΔΨm) assay were used to explore the mechanism of J82 cell apoptosis. Compounds1 and2 had remarkable cytotoxic activities on J82 cell lines with their IC50 values lower than 10 µM concentrations via the mitochondrial apoptotic pathway. Graphical Abstract: